Iodine status in the Nordic countries : past and present - Nyström, Helena Filipsson; Brantsaeter, Anne Lise; Erlund, Iris; Gunnarsdottir, Ingibjörg; Hulthén, Lena; Laurberg, Lena; Mattisson, Irene; Rasmussen, Lone B.; Virtanen, Suvi; Meltzer, Helle Margrete (2016)
Background: Adequate iodine nutrition is dependent on ground water content, seafood, and, as many countries use iodized cow fodder, dairy products. In most countries, salt fortification programs are needed to assure adequate iodine intake. Objectives: The objectives are threefold: 1) to describe the past and present iodine situation in the Nordic countries, 2) to identify important gaps of knowledge, and 3) to highlight differences among the Nordic countries’ iodine biomonitoring and fortification policies. Design: Historical data are compared with the current situation. The Nordic countries’ strategies to achieve recommended intake and urine iodine levels and their respective success rates are evaluated. Results: In the past, the iodine situation ranged from excellent in Iceland to widespread goiter and cretinism in large areas of Sweden. The situation was less severe in Norway and Finland. According to a 1960 World Health Organization (WHO) report, there were then no observations of iodine deficiency in Denmark. In Sweden and Finland, the fortification of table salt was introduced 50–75 years ago, and in Norway and Finland, the fortification of cow fodder starting in the 1950s helped improve the population’s iodine status due to the high intake of milk. In Denmark, iodine has been added to household salt and salt in bread for the past 15 years. The Nordic countries differ with regard to regulations and degree of governmental involvement. There are indications that pregnant and lactating women, the two most vulnerable groups, are mildly deficient in iodine in several of the Nordic countries. Conclusion: The Nordic countries employ different strategies to attain adequate iodine nutrition. The situation is not optimal and is in need of re-evaluation. Iodine researchers, Nordic national food administrations, and Nordic governmental institutions would benefit from collaboration to attain a broader approach and guarantee good iodine health for all.